Structural changes in Medicago truncatula root nodules caused by short-term aluminum stress - Sujkowska-Rybkowska, Marzena (Symbiosis (Philadelphia, Pa.), 2012)
Aluminum in the form of Al3+ is one of the most toxic heavy metal pollutants in nature and its effects are primarily root-related. Roots of Medicago truncatula exposed to 50 μM of AlCl3 for 2 h and 24 h were examined by light and electron microscopy. Changes in the appearance of the host cells, infection threads and bacteroidal tissue occurred during the first 2 h of Al stress. Microscopic observations showed that aluminum: (1) induced thickening of plant cell and infection threads (ITs) walls, (2) stimulated IT enlargement, (3) caused disturbances in bacterial release from the ITs, (4) modified cell vacuolation and induced synthesis of granular material and its deposition in the cytoplasm, (5) and caused structural alterations of organella and bacteroids